OP0057 Fluorescence optical imaging in juvenile idiopathic polyarticular disease before and during antirheumatic treatment. (15th June 2017) - Klein, A; Just, G-W; Werner, SG; Becker, I; Oommen, P; Minden, K; Langer, H-E; Horneff, G
Abstract : Background: Valid detection of inflamed joints is essential for correct classification, therapeutic decisions and assessment of treatment efficacy in juvenile idiopathic arthritis (JIA). Objectives: Fluorescence optical imaging (FOI) enables visualization of inflammation in arthritis of finger and hand joints and might be used in JIA. Methods: A 24-week observational study in polyarticular JIA patients newly starting treatment with either methotrexate or a biologic was performed. Patients were evaluated clinically, by ultrasound B–mode, power-Doppler and FOI at baseline, week 12 and 24. Results: Of 37 patients enrolled, 24 patients started MTX and 13 a biologic for the first time (Etanercept n=11, Adalimumab and Tocilizumab one 1). Composite measures, mean JADAS 10 decreased significantly from 17.7 at baseline to 12.2 and 7.2 at week 12 and 24 respectively and JIA-ACR 30/50/70/100 response rates at week 24 were 85%/73%/50%/27%. In total 1110 joints were examined clinically, 990 by US/PD and 990 by FOI. At baseline/week12/week24 23.6%/16.4%/9.0% joints on hand and fingers were clinically active joints, by US 19.4%/16.1%/11.5% joints showed effusions, 18.8%/12.7% and 9.6% showed synovial thickening and by PD 6.9%/1.8%/5% joints showed hyperperfusion. Any sign of arthritis was detected by US/PD in 24.5%/19.2%and17%. By FOI at 38.7%/29.2%/27.6% showed a signal enhancement in at least one phase. Summarizing all 3 points of time, the highest numbers of signals were detected by FOI with 32% of joints, especially in phase 2 while by US/PD 20.7% and by clinical examination 17.5% were active. A high number of joints (21.1%) had FOI signals but were clinically inactive. 20.1% of joints with signals in FOI did not show effusion, synovial thickening or hyperperfusion by US/PD. Due to the high number of negative results specificity of FOI compared to clinical examination/US/PD was high (84–95%), sensitivity was moderate only. Conclusions: Improvement upon treatment with either methotrexate or a biologic can be visualized by FOI. FOI and US/PD could detect clinical but also subclinical inflammation. FOI detected subclinical inflammation in higher extent than US. Disclosure of Interest: None declared